MODERN APPROACHES TO TRANSLATION, COMMUNICATION, AND LANGUAGE PRACTICE - SALIHOVA , Sogdiana Erikovna; TO’YMURODOVA, Rayhona Mehriddinovna (The Lingua Spectrum, 2025)
In today’s globalized world, translation is no longer just about changing words from one language to another, it has become a vital form of intercultural communication. Modern translation focuses on context, the purpose of the message, and cultural differences, making it an important tool for clear and effective interaction. This article examines current translation theories and their effect on communication and also how language practice helps develop cultural understanding.